Design of a Website-Based New Learner Admission Information System at SD Kristen 2 Purwokerto - Nasution, Heskia; Wibowo, Adhi; Widiastuti, Rosalina Yani; Suyudi (Journal of Intelligent Systems and Information Technology, 2025)
This research designs and implements a web-based PPDB Information System at SD Kristen 2 Purwokerto to overcome data inaccuracies, the risk of losing documents, and administrative inefficiencies due to manual systems. The system was developed using UML modeling, including use case, activity, and class diagrams, and enables more efficient and transparent online registration. The results of testing with Black Box Testing (Equivalence Partitioning) show that the system functions according to specifications. Testing the main features of login, registration, student enrollment, payment verification, and admin and principal data management produced appropriate outputs, improved efficiency and data accuracy, and strengthened system security. The system is proven to improve the quality of education services, with suggestions for the development of automatic notification features, user support, and improved data security to maintain the integrity of student information.